TECHNICAL SKILL, WORK EXPERIENCE, WORK DISCIPLINE AND ITS INFLUENCE ON CRAFTSMEN PERFORMANCE AT POTTERY CLUSTER IN TULUNGAGUNG REGIONS - Arga Christian Sitohang; Hendy Widiastoeti (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose- This study was aimed to determine the influence of technical skills, work experience, work discipline on the performance of craftsmen in the pottery cluster in Tulungagung Regency. Design/Methodology/Approach- The population in this study were 35 pottery craftsmen who had more than 2 years of work experience. The sampling technique use complete enumeration method where all members of the population are used as respondents. Using primary data related to technical skills, work experience, work discipline and their impact on the pottery craftsmen's performance. While the analysis tool uses multiple linear regression analysis. Findings-The results of the study show that technical skill, work experience, and work discipline have positive and significant effect on the craftsman's performance in the pottery cluster in Tulungagung Region. Practical Implication- many workers lack of discipline at work and less innovate in form of creating new product. Meanwhile most of the owner of small bussiness had years in experience inherited from their parents.